2008
DOI: 10.1103/physrevb.77.064106
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of kinks on screw dislocation in silicon

Abstract: Theoretical calculations of the structure, formation and migration of kinks on a non-dissociated screw dislocation in silicon have been carried out using density functional theory calculations as well as calculations based on interatomic potential functions. The results show that the structure of a single kink is characterized by a narrow core and highly stretched bonds between some of the atoms. The formation energy of a single kink ranges from 0.9 to 1.36 eV, and is of the same order as that for kinks on par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 57 publications
6
32
0
Order By: Relevance
“…Finally, the main factor comes from the large difference between migration energies. While W m is large for partials, due to complex reorganization of atomic bonds [24], it is at least one order of magnitude lower for the screw dislocation because in that case, kink migration occurs by breaking and formation of a single highly stretched bond [22]. Therefore, it is simply the inclusion of migration energies that drastically changes the results compared to the Duesbery and Joós model.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…Finally, the main factor comes from the large difference between migration energies. While W m is large for partials, due to complex reorganization of atomic bonds [24], it is at least one order of magnitude lower for the screw dislocation because in that case, kink migration occurs by breaking and formation of a single highly stretched bond [22]. Therefore, it is simply the inclusion of migration energies that drastically changes the results compared to the Duesbery and Joós model.…”
mentioning
confidence: 96%
“…For non-dissociated dislocations, to our knowledge, no experimental data are available for kinks. Nevertheless, kinks on a non-dissociated shuffle screw dislocation have been recently investigated by means of first principles and atomistic potential simulations, taking advantage of the Nudged Elastic Band method [22]. These calculations indicated that the kink formation energy ranges from 0.90 eV to 1.36 eV, whilst the migration energy is very low, and ranges from 20 meV to 160 meV.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The further propagation of the kinks along the dislocation line is responsible for the glide of the whole dislocation. The theoretical description of dislocation motion involving the kink-pair mechanism was successfully applied to the understanding of elemental deformation processes (see, for instance, [81]) in several materials, including bcc metals [82][83][84][85][86][87][88][89], covalent materials such as silicon [90][91][92] and ionic materials [93][94][95], including MgO [23].…”
Section: The Kink-pair Mechanismmentioning
confidence: 99%